Makna dan Peran Tradisi Nyadran dalam Kehidupan Sosial Keagamaan Masyarakat Jawa: Studi Kasus di Sidoarjo - Alivia Anjelita Syafa Rizqi; Agus Machfud Fauzi (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2025)
The Nyadran tradition is one of the religious and cultural rituals that has been going on for a long time and is still maintained by the Javanese people, including in Sidoarjo Regency. Amidst the dynamics of social change and modernization, the continuity of the Nyadran tradition has become an interesting phenomenon to study, especially in relation to how people interpret and practice it in contemporary socio-religious life. This study aims to analyze the meaning and role of the Nyadran tradition in the socio-religious life of the Javanese community in Sidoarjo Regency. This study uses a qualitative method with an ethnographic approach. Data collection was carried out through participant observation, in-depth interviews with community leaders, religious leaders, and residents directly involved in the implementation of Nyadran, as well as documentation studies. Data analysis uses Max Weber's social action theory to understand the motives and subjective meanings of people's actions in following the Nyadran tradition, as well as Clifford Geertz's symbolic theory to interpret Nyadran as a symbolic system that represents and shapes the Javanese people's worldview. The results of the study show that the Nyadran tradition has multidimensional meanings. Spiritually, Nyadran is understood as a form of respect and prayer to ancestors as well as a means of self-reflection in preparing to welcome the holy month of Ramadan. Socially, this tradition functions as a mechanism for strengthening solidarity, mutual cooperation, and social equality through collective practices such as cleaning graves, praying together, and holding feasts. Culturally, Nyadran plays an important role in preserving local values and maintaining Javanese cultural identity amid the tide of modernization. Thus, Nyadran not only survives as a cultural heritage, but also as a dynamic and relevant socio-religious practice in the lives of modern Javanese society.